2017
DOI: 10.4103/jomfp.jomfp_22_17
|View full text |Cite
|
Sign up to set email alerts
|

Juxtaoral organ of Chievitz: An innocuous organ to be known

Abstract: The Juxtaoral Organ of Chievitz is a normal anatomical structure located within the soft tissue in the buccotemporal fascia on the medial surface of the ascending ramus. This enigmatic vestigial structure is considered to be of neuroepithelial origin with no known function. As a matter of fact, JOOC is one of the most treacherous pitfalls in surgical pathology with respect to lesions in the head and neck area. Hence the basic aim of this short communication is to reveal the importance about this organ and enli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…In our case the JOO appeared bilaterally, which agrees with what was described by Ito et al [10] and Sancheti et al [24], while the location and relations observed are consistent with what has been established in the literature [2,16,25], ruling out the possibility that it is an accessory parotid gland, as this presents a more superficial location and is relative to the parotid duct [21]. In our finding we observed a close proximity of the JOO to the roots of lower third molar, which could imply its exposure and/or damage during oral surgeries, although due to the little or no functionality that it seems to have, we consider that this damage might not be relevant to an individual's physiology.…”
Section: Discussionsupporting
confidence: 93%
“…In our case the JOO appeared bilaterally, which agrees with what was described by Ito et al [10] and Sancheti et al [24], while the location and relations observed are consistent with what has been established in the literature [2,16,25], ruling out the possibility that it is an accessory parotid gland, as this presents a more superficial location and is relative to the parotid duct [21]. In our finding we observed a close proximity of the JOO to the roots of lower third molar, which could imply its exposure and/or damage during oral surgeries, although due to the little or no functionality that it seems to have, we consider that this damage might not be relevant to an individual's physiology.…”
Section: Discussionsupporting
confidence: 93%
“…It is generally described as 7–17 mm long and 1–2 mm wide [ 1 , 4 , 12 , 21 ]. In the cases in which the juxtaoral organ reaches 10 mm of diameter, this may be presumed to indicate a submucosal tumour or hyperplasia of the juxtaoral organ [ 10 ].…”
Section: Juxtaoral Organ Anatomymentioning
confidence: 99%
“…This organ was also described as in close proximity to the site used for inferior alveolar nerve block injection [ 24 ]. Other authors reported that the juxtaoral organ is located in the infratemporal region, at the level of the submucosa, in the retromolar trigone, medial to the medial pterygoid muscle and in relation with the pterygomandibular raphe [ 4 , 10 , 15 ]. Ramos-Vega and Roa [ 4 ] used, for the first time, head sections of a plastinated Asian male cadaver.…”
Section: Juxtaoral Organ Anatomymentioning
confidence: 99%
See 2 more Smart Citations